O manto sagrado de jesus: uma estratégia para a recuperação da cidadania - Firmino, Antonio Ricardo Beltrão (2009)
The object of this dissertation is the study of the ways of the youths' attendance in risk situation done by three institutions, a public one and laic and two confessionals, that are Non Government Organizations ONGs - of christian religious shape, being a catholic and other protestant. The general objective of this research was: to analyze the attendance forms for the recovery of the citizenship and youths' inclusion in situation of social and personal risk of three educational institutions, being a public one and laic and two religious, of João Pessoa/PB. This research universe was organized for ends of comparison, in the following way: Group I, referring the adolescents assisted by CFCMPS, that is the laic public institution, and Group II, that includes the youths assisted by Hope Farm and Youth Group, that they are the two religious institutions Catholic and Protestant, respectively. We verified that the attendance of CFCMPS, that belongs to laic and public shape, is fail, disengaged, and has serious problems of lack of physical maintenance and hygiene, and the results in terms of recovery of the citizenship and the youths' inclusion received by this center are null. By other side, the pedagogical work well-founded in christian religiosity of Hope Farm and Youth Group is based by the tripod of the spirituality, work and the youths' harmonious coexistence that is received by her. They are stimulated to they accept and wish your recovery through the religious practice, manual works and hard and rigid behaviorals rules, that are developed in organized environment and maintained by the own young people in recuperation, and, in agreement with the speeches of these young ones whose results are considered highly satisfactory. The authors that inspired this research were: Mircea Eliade (1991), Weber (2007), Gadotti (1984), Zaluar (1997) among others.